2009
DOI: 10.1037/a0013580
|View full text |Cite
|
Sign up to set email alerts
|

Gravity and solidity in four great ape species (Gorilla gorilla, Pongo pygmaeus, Pan troglodytes, Pan paniscus): Vertical and horizontal variations of the table task.

Abstract: Three experiments modeled after infant studies were run on four great ape species (Gorilla gorilla, Pongo pygmaeus, Pan troglodytes, Pan paniscus) to investigate their reasoning about solidity and gravity constraints. The aims were: (a) to find out if great apes are subject to gravity biased search or display sensitivity for object solidity, (b) to check for species differences, and (c) to assess if a gravity hypothesis or more parsimonious explanations best account for failures observed. Results indicate that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 41 publications
(76 reference statements)
3
38
0
Order By: Relevance
“…These subjects all failed to reason about the location of a hidden barrier when reaching for an invisibly displaced object, but evidenced sensitivity to solidity information in expectancy violation paradigms (Spelke et al 1992;Berthier et al 2000;Hood et al 1999;Santos 2004;Santos et al 2006). Our results, however, do accord with the Wndings of Cacchione et al (2009) indicating that apes act in accordance with solidity and proximity information in conjunction in tasks requiring judgments regarding object movement in horizontal trajectories. Additionally, these results suggest that dogs in this paradigm understood invisible displacement.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…These subjects all failed to reason about the location of a hidden barrier when reaching for an invisibly displaced object, but evidenced sensitivity to solidity information in expectancy violation paradigms (Spelke et al 1992;Berthier et al 2000;Hood et al 1999;Santos 2004;Santos et al 2006). Our results, however, do accord with the Wndings of Cacchione et al (2009) indicating that apes act in accordance with solidity and proximity information in conjunction in tasks requiring judgments regarding object movement in horizontal trajectories. Additionally, these results suggest that dogs in this paradigm understood invisible displacement.…”
Section: Discussionsupporting
confidence: 44%
“…Researchers have observed comparable dissociations between expectancy violation and search paradigms with some adult non-human primates in tasks where subjects are required to reach for objects that undergo interactions with other objects (e.g., Hauser 2001;Hauser et al 2001;Santos and Hauser 2002;Santos 2004;Santos et al 2006). In contrast to these results, Cacchione et al (2009) recently observed that apes successfully utilized solidity and proximity information in conjunction to make correct choices about object movement along horizontal trajectories. However, it is unclear whether apes would have been successful using solidity information alone.…”
Section: Introductionmentioning
confidence: 99%
“…However, when the object was dropped behind a screen onto an occluded shelf, both groups show a bias for searching beneath the shelf, perhaps owing to experience inducing an overgeneralized expectation for objects to be located at ground level. Older children (2.5-3 years) and mature apes show evidence of being able to overcome this bias and search in the correct location [74,76]. In other problem-solving contexts, both monkeys and infants show perseverative reaching (i.e.…”
Section: (A) Adjusting Phenotypic Biasesmentioning
confidence: 99%
“…Taken as a whole, the picture could be interpreted as failure to inhibit an early established principle (straight‐down fall), with the implication that progress depends upon greater inhibitory control. Interpretations of this kind have already appeared in the literature (e.g., Cacchione, Call, & Zingg, ; Hood et al ., ), no doubt with recognition that they bring object fall into line with much contemporary theorizing in developmental psychology.…”
Section: Introductionmentioning
confidence: 83%